ANALYSIS OF THE RELATIONSHIP MODEL OF ORGANIZATIONAL JUSTICE AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR: EVIDENCE FROM THE INDONESIAN BANKING SECTOR - Setiyawami Setiyawami; Christina Bagenda; Hernansi Biso; Trisnia Manggiasih (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2024)
This research aims to analyze the influence of transformational leadership, self-efficacy, and organizational climate on innovative work behavior in manufacturing companies in Indonesia. This research uses a literature and field design with a causal associative approach. This study uses a research instrument test consisting of validity and reliability tests. The quantitative analysis consists of a normality test, regression test, hypothesis test, correlation test, and coefficient of determination. This research concludes that transformational leadership, self-efficacy, and organizational climate have a positive and significant effect on innovative work behavior. In the ever-growing digital era, transformational leadership is essential for manufacturing companies to face challenges and take advantage of emerging opportunities. In the digital era, self-efficacy helps employees cope with uncertainty and change, turn challenges into opportunities, and view technological change as a foundation for personal and professional growth. Furthermore, by adopting a pro-innovation organizational climate, manufacturing companies can more easily adapt to technological changes, optimize production processes, and exploit the full potential of the Industrial Revolution 4.0.